2013
DOI: 10.1007/s40336-013-0005-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of [18F]DOPA PET and PET/CT in patients with neuroendocrine tumors: a meta-analysis

Abstract: The aim of this study was to systematically review and meta-analyze published data on the diagnostic accuracy of positron emission tomography (PET) using fluorine-18-dihydroxyphenylalanine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
1
14
0
2
Order By: Relevance
“…Therefore, 18 F‐DOPA PET/CT could be useful in patients with MEN‐2 syndromes who often present with 18 F‐DOPA‐accumulating medullary thyroid carcinoma and pheochromocytoma simultaneously (Treglia et al ., ; Taieb et al ., ). On the other hand, the overall accuracy of this method in detecting GEP‐NETs associated with MEN‐1 syndrome, and in particular pancreatic NETs, seems to be lower than that of somatostatin receptor PET (Treglia et al ., ; Balogova et al ., ; Santhanam & Taieb, ) (Rufini et al ., ).…”
Section: Role Of 18f‐dihydroxyphenylalanine (18f‐dopa)mentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, 18 F‐DOPA PET/CT could be useful in patients with MEN‐2 syndromes who often present with 18 F‐DOPA‐accumulating medullary thyroid carcinoma and pheochromocytoma simultaneously (Treglia et al ., ; Taieb et al ., ). On the other hand, the overall accuracy of this method in detecting GEP‐NETs associated with MEN‐1 syndrome, and in particular pancreatic NETs, seems to be lower than that of somatostatin receptor PET (Treglia et al ., ; Balogova et al ., ; Santhanam & Taieb, ) (Rufini et al ., ).…”
Section: Role Of 18f‐dihydroxyphenylalanine (18f‐dopa)mentioning
confidence: 97%
“…Therefore, 18 F-DOPA PET/CT could be useful in patients with MEN-2 syndromes who often present with 18 F-DOPA-accumulating medullary thyroid carcinoma and pheochromocytoma simultaneously Taieb et al, 2014). On the other hand, the overall accuracy of this method in detecting GEP-NETs associated with MEN-1 syndrome, and in particular pancreatic NETs, seems to be lower than that of somatostatin receptor PET (Treglia et al, 2012a;Balogova et al, 2013;Santhanam & Taieb, 2014) (Rufini et al, 2013b). 18 F-DOPA PET has been found to be the best overall imaging modality in the localization of pheochromocytomas related to MEN-2 syndromes, but the availability of this radiopharmaceutical is limited (Pacak et al, 2009).…”
Section: Role Of 18 F-dihydroxyphenylalanine ( 18 F-dopa)mentioning
confidence: 99%
“…[9][10][11][12][13] Nevertheless, experience with somatostatin receptor PET in recurrent MTC is limited compared to other NETs. Furthermore, while previous evidence-based articles have assessed the detection rate (DR) of PET using 18 F-FDG 14,15 and 18 F-DOPA 16,17 in recurrent MTC, a meta-analysis evaluating the DR of somatostatin receptor PET in recurrent MTC is still lacking. Therefore, we aimed to perform a systematic review and a meta-analysis on the DR of somatostatin receptor PET or PET/computed tomography (PET/CT) in patients with recurrent MTC to add evidence-based data to this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Somatostatin receptor PET/CT has been demonstrated to be superior compared to somatostatin receptor scintigraphy in evaluating lung NETs, due to the superior spatial resolution of PET imaging [6]. Furthermore, 68 Ga-somatostatin analogues provided better results compared to the radiolabelled amino acid 18 Fdihydroxyphenylalanine (DOPA) in evaluating lung NETs [6], but literature reports specifically addressing the use of 18 F-DOPA in pulmonary NETs are few [11]. Since different information may be obtained using various PET tracers, some authors have recently reported preliminary results on dual-tracer PET/CT imaging using 68 Ga-somatostatin analogues and 18 F-FDG in well-differentiated pulmonary NETs [12][13][14][15].…”
mentioning
confidence: 99%